2015
DOI: 10.1186/s12888-015-0474-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of structured decision making on absconding by forensic psychiatric patients: results from an A-B design study

Abstract: BackgroundFew studies have investigated absconding from forensic hospitals and there are no published studies of interventions aimed at reducing these incidents in forensic settings. We present a study of the impact of a new policy using structured professional judgment and an interdisciplinary team-based approach to granting privileges to forensic patients. We assess the impact of this policy on the rate and type of absconding from a metropolitan forensic facility.MethodsFollowing concern about the rate of ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(89 citation statements)
references
References 35 publications
2
87
0
Order By: Relevance
“…The causes of patient absconding include fear, homesickness, irritation, concerns about family responsibilities, delayed medical examinations and treatments, treatment costs, lack of insurance coverage, lack of information about the disease, and mental disorders (3,15,(17)(18)(19). According to a study by Handel et al, reducing the waiting time for patients and informing them about the approximate waiting time can dissipate the number of escapes (20).…”
Section: Introductionmentioning
confidence: 99%
“…The causes of patient absconding include fear, homesickness, irritation, concerns about family responsibilities, delayed medical examinations and treatments, treatment costs, lack of insurance coverage, lack of information about the disease, and mental disorders (3,15,(17)(18)(19). According to a study by Handel et al, reducing the waiting time for patients and informing them about the approximate waiting time can dissipate the number of escapes (20).…”
Section: Introductionmentioning
confidence: 99%
“…Three explored the patient experience of absconding, specifically relating to patient perspectives of treatment and involuntary commitment 357–359. One study explored staff perspectives of absconding management techniques,360 and two studies evaluated interventions to reduce absconding rates; both were found to be effective 361 362. Two studies focused on wandering behaviour in women with dementia, linking wandering to physical environment factors, such as light, sound, crowding363 and falls 364.…”
Section: Resultsmentioning
confidence: 99%
“…At Level 2, consistency applies only within teams with some consistency through the use of international diagnostic systems and manualized treatment programs. At Level 3, hospital or service-wide governance is applied to essential decision making and processes such as applying admission criteria by admission panels (6569), to plan care pathways across the service, with evidence-based decision making on matters such as care systems (7073), leave (74, 75), and reports to mental health review tribunals (7678). At Level 3, precision medicine can be practiced with diagnosis refined into the staging of progression of illnesses and outcomes (79).…”
Section: Seven Domainsmentioning
confidence: 99%